Combined multidirectional plyometric and balance training enhances neuromuscular, postural and sport-specific performance in soccer players: a randomized controlled trial - Nawahda, Y.; Paillard, T.; Abubshara, J.; van den Tillaar, R.; Jlid, M. C. (Frontiers in Physiology, 2026)
Purpose: This study examined the effects of combining multidirectional plyometric training with balance exercises performed on an unstable surface on neuromuscular performance, dynamic postural control, inter-limb balance asymmetry, and sport-specific motor skills in U17 soccer players. Forty-five male youth soccer players (16-17 years) were randomly assigned to a combined plyometric and balance training group (n = 15), a plyometric training group (n = 15), or a control group (n = 15). The intervention lasted 8 weeks, with three sessions per week. Assessments included squat jump, countermovement jump, drop jump, 10-, 20-, and 30-m sprint, reactive agility, Y-Balance Test performance, inter-limb asymmetry, slalom dribble, and wall-pass tests. Both experimental groups improved significantly in sprint, jump, dynamic balance, and sport-specific motor skill performance compared with the control group (p < 0.05). No significant between-group differences were found for jump performance. Reactive agility improved significantly more in the combined group than in the plyometric group. Dynamic postural control improved in both training groups, with greater gains in the combined group in the anterior and posteromedial directions for both dominant and non-dominant legs. Inter-limb asymmetry decreased in all three directions in the combined group, whereas the plyometric group improved only in the anterior and posterolateral directions. In sport-specific motor skills, both training groups improved, although no significant difference was found between the plyometric and control groups in the wall-pass test. Combined training appears to provide additional benefits for reactive agility, selected balance measures, inter-limb asymmetry and sport-specific skills in youth soccer players.